Optimum Distribution of Power by Intelligent Fuzzy Sets Analyzer and Controller - M, Karthikeyan; Muthu Vijaya Pandian, S; ., . (International Journal of Engineering and Technology, 2018)
Meeting increasing demand for the electrical power without changing the existing infrastructure is a challenging issue. The transmission and the distribution are always struggling with losses in our ac power system networks. In this research an intelligent fuzzy logic approach is to be used for power system operation and control in distribution management. The VAR compensating devices like OLTC, SVC are to be controlled by the fuzzy expert system for modifying reactive power. The fuzzy membership functions, fuzzy rules are to be displayed. A co-ordination control between these VAR compensating devices using fuzzy logic control is to be discussed. An optimum location and the proper design of a capacitor banks for reducing the harmonic injection in the power system is to be suggested. The validity of this approach is to be given by the comparison graphs. All the simulations are to be carried out by MATLAB software. This research will investigate the effects of arising problems in an ac power system distribution without changing the existing infra structure. The various types of problems arising in a power system are to be listed. Among these the voltage stability in the buses has got the top priority. The solutions for reducing the power congestion created by these arising problems can be carried out.Â Â